SUMPs implementation: Designation of capacity gaps of local authorities in the delivery of sustainable mobility projects - Kalakou, S. (2021)
There are numerous initiatives at the European level that are aimed at increasing the capacity of cities with regard to sustainable mobility planning by developing guidelines and various forms of training materials. An important prerequisite for systematic capacity building is to understand what capacity actually means in the context of mobility planning and which concrete factors influence the ability to shape and deliver sustainable mobility solutions. In the SUITS EU project, a tool for capacity assessment was developed and tested with six participant cities. Through interviews and workshops with mobility stakeholders in the participating cities, 15 challenges that the cities face while planning and implementing mobility plans were identified and led to the design of a set of 54 indicators that assess the capacity of an authority to develop and implement a mobility plan. The presented methodology enables authorities to self-assess their performance and capacity and identify the sources of the problems they face and that are impeding their effectiveness in developing and implementing mobility plans. The application in the six participating cities demonstrated that the evaluation tool here introduced is comprehensive, encompasses all the aspects of the environment in which a local authority (LA) operates and effectively highlights the areas where interventions are required so that the LAs can systematically increase their capacity.